Electronic Cigarette Toxicity - J. Drew Payne; David Michaels; Menfil Orellana-Barrios; Kenneth Nugent (SAGE Publishing, 2017)
Electronic cigarettes (e-cigarettes) are often advertised as a healthier product when compared with traditional cigarettes. Currently, there are limited data to support this and only a threat of federal regulation from the US Food and Drug Administration. Calls to poison control centers about e-cigarette toxicity, especially in children, and case reports of toxic exposures have increased over the past 3 years. This research letter reports the frequency of hazardous exposures to e-cigarettes and characterizes the reported adverse health effects associated with e-cigarette toxicity.